An amorphous ultrathin iridium/carbon catalyst realizing efficient electrochemical hydrogen evolution. Issue 37 (19th April 2022) - Hao, Jing; Hou, Jie; Wei, Hehe; Su, Zixiang; Li, Hui; Zhang, Longtao; Gong, Xueqing
Abstract : An amorphous 1.1 nm Ir/C catalyst exhibits an ultralow 10 mV overpotential, 117 A mg −1 mass activity and outstanding long-term durability, superior to those of the commercial Pt/C catalyst. Abstract : An amorphous 1.1 nm Ir/C catalyst exhibits ultralow overpotentials of 10 and 64 mV for the hydrogen evolution reaction at current densities of 10 and 100 mA cm −2, together with 117 A mg −1 mass activity and outstanding long-term durability, superior to those of the commercial Pt/C catalyst.